A RANDOMNESS‐BASED THEODICY FOR EVOLUTIONARY EVILS. Issue 4 (26th November 2017) - Wessling, Jordan; Rasmussen, Joshua
Abstract: We develop and knit together several theodicies in order to find a more complete picture of why certain forms of (nonhuman) animal suffering might be permitted by a perfect being. We focus on an especially potent form of the problem of evil, which arises from considering why a perfectly good, wise, and powerful God might use evolutionary mechanisms that predictably result in so much animal suffering and loss of life. There are many existing theodicies on the market, and although they offer helpful resources, we combine and further develop several proposals to produce a composite theodicy that avoids certain shortcomings of the individual theodicies. An important element of our project is locating a role for randomness in cosmic and biological evolution. In particular, we show how randomness might enhance or enable certain goods, including everlasting goods, at the risk of temporary evils.